Doing Business Economy Profile 2017 : United Kingdom - World Bank Group (World Bank, Washington, DC, 2016)
This economy profile presents the Doing Business indicators for United Kingdom. To allow useful comparison, it also provides data for other selected economies (comparator economies) for each indicator. Doing Business 2017 is the 14th in a series of annual reports investigating the regulations that enhance business activity and those that constrain it. Economies are ranked on their ease of doing business; for 2016 United Kingdom ranks 6. Doing Business sheds light on how easy or difficult it is for a local entrepreneur to open and run a small to medium-size business when complying with relevant regulations. It measures and tracks changes in regulations affecting 11 areas in the life cycle of a business: starting a business, dealing with construction permits, getting electricity, registering property, getting credit, protecting minority investors, paying taxes, trading across borders, enforcing contracts, resolving insolvency, and labor market regulation. Doing Business 2017 presents the data for the labor market regulation indicators in an annex. The report does not present rankings of economies on labor market regulation indicators or include the topic in the aggregate distance to frontier score or ranking on the ease of doing business. The indicators are used to analyze economic outcomes and identify what reforms have worked, where, and why. The data in this report are current as of June 1, 2016 (except for the paying taxes indicators, which cover the period January-December 2015).